Reiter's disease in three boys. - Iveson, J M (1975)
Three cases of Reiter's disease occurring in boys under the age of 16 are reported. One of these presented with a Salmonella enteritidis diarrhoea. This conforms to the 'dysenteric' form of Reiter's disease usually seen in Europe and rarely reported in England. Another presented with a monarticular arthritis of the knee, and the third has developed a chronic relapsing erosive arthritis as a result of sexually acquired Reiter's disease--an occurrence not previously reported in this age group. We draw attention to the frequency of diarrhoea in these children and the sex incidence of 1 female to 4--5 males, which agrees more with Reiter's disease of dysenteric origin than that acquired venereally.